Endothelial dysfunction in children with type 1 diabetes mellitus - Nascimento,Antonella Márcia Mercadante de Albuquerque do (2017)
ABSTRACT Objective The purpose of this study was to verify the presence of endothelial dysfunction and initial structural atherosclerotic changes in children with Type 1 diabetes mellitus (T1DM). Subjects and methods The study population comprised 31 diabetic children aged 6 to 12 years, divided into two subgroups according to the duration of the T1DM diagnosis: subgroup 1, with less than 5 years elapsed since diagnosis, and subgroup 2, with more than 5 years elapsed since diagnosis. The control group comprised 58 age-matched healthy children. Ultrasonographic techniques were used to measure the flow-mediated dilatation (FMD) of the brachial artery and the intima-media thickness (IMT) of the carotid arteries. Results Children with T1DM with longer disease duration showed significantly decreased mean values of FMD compared with those in the control group. No significant differences between the groups were found in relation to IMT. The FMD percentage presented a moderate negative correlation with glycated hemoglobin (HbA1c) and fasting glucose levels. Conclusion Our findings suggest that endothelial dysfunction may be already present in children with 5 years or more elapsed since diagnosis, even in the absence of atherosclerotic structural changes. The decreased vasodilation response correlated with hyperglycemia.